Pliocene marine Bivalvia of Vale do Freixo (Pombal, Portugal): updated taxonomic list and discussion - Pimentel, Ricardo Jorge (2021)
The exceptional Pliocene marine faunal assemblages of west central Portugal have been known since the late 19th century. They include highly diverse molluscan faunas whose study is far to be completed. Discovered nearly 40 years ago, Vale do Freixo (Carnide, Pombal) is perhaps the most outstanding fossil site. Neverthless, the bivalves remain relatively unknown. This study focuses on the taxonomy of this relevant group of marine Mollusca. The research, based on a detailed sampling of three fossiliferous beds from the Carnide Formation, yielded a list of 85 species belonging to 75 genera and 32 families. Forty-three species are new for the Carnide area and twenty-three are reported for the first time in the Portuguese Pliocene, increasing to 115 the number of known species in the Mondego Basin in the Beira Litoral.